Efektivitas Penerapan Model Two Stay Two Stray dalam Pembelajaran Tematik di MI Al-Huffadz Kecamatan Tellu Siattinge Kabupaten Bone - Faisal Gn, Fafang; Rasyid, Nirwana (Madrasah Ibtidaiyah Research Journal, 2023)
This research aims to determine the implementation of the two stay two stray model in thematic learning at MI Al-Huffadz Tellu Siattinge District Bone Regency, the supporting and inhibiting factors for the implementation of the two stay two stray model, and the solution to the inhibition of the application of the two stay two stray model in learning. This type of research is descriptive qualitative research. The data collection techniques used are: observation, interview, and documentation. As well as the data analysis technique used by using steps starting from reducting the data, describing the data, and verifying the data as a conclusion. The results of this research indicate that: First, the application of two stay two stray model at MI Al-Huffadz Tellu Siattinge District Bone Regency has been implemented properly. The two stay two stray model is a variation of the learning model that is the choice for existing teachers at MI Al-Huffadz because by applying this learning model the teaching and learning process can be effective, active, and fun. Second, the supporting factors for the implementation of the two stay two stray model in MI Al-Huffadz Tellu Siattinge District Bone Regency namely student interest in learning and the role of teachers in directing, guiding, and motivating students. While the inhibiting factor is the number or quantity of students still small. Third, the solution to the inhibiting factors of implementing the two stay two stray model in thematic learning at MI Al-Huffadz Tellu Siattinge District Bone Regency, namely by providing good motivation, direction, and guidance to students and the role of the teacher as a good role model in the classroom.